Pengaruh Fasilitas, Lokasi Dan Harga Terhadap Kepuasan Tamu Menginap di Hotel Neo Denpasar - Ni Made Dian Pratiwi; Ni Made Hartini (Journal Research of Management, 2026)
The purpose of this study is to examine how the Neo Denpasar Hotel's facilities, location, and price affect visitors' satisfaction.  Quantitative descriptive research methodologies are used in this study.  The purposive sampling research method is the sampling strategy employed in this study.  Multiple linear regression analysis is used in research using SPSS 25 for Windows.  90 people participated in this study.  The study's sample consisted of visitors who had previously stayed at the Neo Denpasar Hotel.  Respondents must be at least 17 years old and deemed capable of delivering information consistent with the facts as they stand.  A questionnaire was used to gather information. The research results show that facilities, location, and proce have a positive and significant influence on guest satisfaction when staying at the Neo Denpasar Hotel.